PENDIDIKAN ANAK DALAM KELUARGA SEBAGAI BENTUK PERLINDUNGAN ANAK DALAM PERSPEKTIF AL-QUR’AN - Indriyati, Anisa (Musawa Jurnal Studi Gender dan Islam, 2011)
Children are an important part of a family, and their condition within the family is consequential to their condition in the society and nation. There are many issues regarding children, one of them being allegations of violence committed against them. The efforts to reduce such violence require an effort to religious understanding through the Quran with respect to the protection of children, by elucidating rights and responsibilities. This effort is also support by Law no. 23/2003 on Protection of Children Â